Clinical And Biochemical Outcomes Of Sodium-Glucose Co-Transporter-2 (SGLT2) Inhibitors In Type 2 Diabetes Mellitus Patients - Saleem, Muhammad (J Endocr Soc, 2021)
Background: SGLT-2 inhibitors are a group of oral medications that work independently of insulin working as anti-diabetics by enhancing the excretion of glucose. The purpose of our study was to assess the improvement in terms of HbA1c, weight, blood pressure and BMI and the hepatics and renal effect in terms of SGPT and Creatinine in patients already on three oral glucose lowering agents when SGLT-2 inhibitor was added to their medications. Methods: This retrospective, real world, single center study included 99 patients (mean age [Standard Deviation]: 53.8 [9.63] years) with poorly control type 2 diabetes. Data was recorded at three times, before the addition of SGLT-2 inhibitor and then at 3 and 6 month follow up after the drug had been added in patient’s medications. Physical parameters namely weight, BMI and blood pressure were recorded in the clinic while HbA1c, SGPT and Creatinine were checked by laboratory. Results: Improvement was seen in all parameters at both 3 and 6 month follow up interval. The reduction in HbA1c was statistically significant (P-value < 0.001) with (Mean Reduction [Standard Deviation)) 0.81[1.02] % at 3 months and 1.07[1.11] % at 6 months. Weight was also significantly reduced (P-value < 0.001) with (MR [SD]) 1.83[2.32] kg at 3 and 4.02[6.04] kg at 6 months. Statistically significant reduction (P-value < 0.001) in BMI was also seen with 0.69[0.95] kgm(-2) at 3 months and 2.13[3.41] kgm(-2) at 6 months of follow up. The systolic blood pressure showed significant reduction (P-value < 0.05) of 5.9[15.76] mmHg at 3 months and 6.37[18.33] mmHg at 6 months. The creatinine and SGPT values of the patient showed minimal variation over the course of these 6 months of follow up. Conclusion: Our study showed that SGPT-2 can be reliably used in patients in which diabetes is not being controlled by other glucose lowering agents and is safe for use in patients in which hepatic and renal function needs to be preserved. Keywords: SGLT-2 inhibitors, Type 2 Diabetes Mellitus, Pakistan